Rethinking Ecology – Challenging Current Thinking in Ecological Research - Stephane Boyer; Marie-Caroline Lefort; Linton Winder (Rethinking Ecology, 2016)
Rethinking Ecology is a new open access, peer-reviewed journal that aims at fostering both forward-thinking and the publication of novel ideas in all aspects of ecology, evolution and environmental science. This editorial briefly presents the rationale, unique features and the aspiration of the journal.